Circulating microRNAs and collateral circulation in coronary chronic total occlusion - A. V. Kiseleva; E. A. Sotnikova; V. A. Kutsenko; A. A. Zharikova; A. I. Ershova; A. N. Meshkov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Coronary collateral circulation (CCC) above the coronary chronic total occlusion is an alternative blood supply to the ischemic myocardium and increases survival among patients with coronary artery disease. In this regard, identification of novel markers associated with the CCC severity has diagnostic potential for patient stratification. It has been shown that circulating microRNAs play an important role in almost all cardiovascular aspects, including the association of some microRNAs with the CCC severity. The aim of this review is to consider the main modern studies on association of circulating microRNAs and CCC severity in coronary chronic total occlusion in patients with coronary artery disease, followed by a functional analysis of the identified microRNAs.